Healing Faith: A Qualitative Exploration of Latina Breast Cancer Survivors. Issue 2 (October 2016) - Barden, Sejal M.; Gutierrez, Daniel; Gonzalez, Jessica; Ali, Shainna
Abstract : Latina cancer survivors report higher levels of distress and depression and lower levels of social quality of life and overall health‐related quality of life when compared with all other cancer survivors. Cultural values influence cancer survivorship; however, little research to date has examined how aspects of the Latina culture may be healing during the cancer journey. Therefore, the purpose of this article is to present findings from a qualitative study exploring the influence of culture on quality of life for Latina breast cancer survivors. The authors use consensual qualitative research to understand the lived experiences of Latina breast cancer survivors.